2016
DOI: 10.1101/080648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The duration of mitosis and daughter cell size are modulated by nutrients in budding yeast

Abstract: The size of nearly all cells is modulated by nutrients. Thus, cells growing in poor nutrients can be nearly half the size of cells in rich nutrients. In budding yeast, cell size is thought to be controlled almost entirely by a mechanism that delays cell cycle entry until sufficient growth has occurred in G1 phase. Here, we show that most growth of a new daughter cell occurs in mitosis. When the rate of growth is slowed by poor nutrients, the duration of mitosis is increased, which suggests that cells compensat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 25 publications
5
51
1
Order By: Relevance
“…In previous studies we discovered that PP2A Rts1 is required for nutrient modulation of cell size [2,18]. Here, we found that PP2A Rts1 controls signaling in the TORC2 network, and that signals from the TORC2 network are required for normal control of cell size.…”
Section: Normal Control Of Cell Size Is Dependent Upon Ceramidessupporting
confidence: 51%
See 4 more Smart Citations
“…In previous studies we discovered that PP2A Rts1 is required for nutrient modulation of cell size [2,18]. Here, we found that PP2A Rts1 controls signaling in the TORC2 network, and that signals from the TORC2 network are required for normal control of cell size.…”
Section: Normal Control Of Cell Size Is Dependent Upon Ceramidessupporting
confidence: 51%
“…In previous work, we discovered that PP2A Rts1 , a form of PP2A associated with the Rts1 regulatory subunit, is required for nutrient modulation of cell size [18]. In addition, inactivation of PP2A Rts1 abolishes the linear relationship between cell size and growth rate [2]. Together, these observations suggest that PP2A Rts1 could play an important role in mechanisms that control cell growth and size.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations